Victim representation for sexual history evidence in Ireland: A step towards or away from meeting victims’ procedural justice needs? - Iliadis, Mary (Criminology & criminal justice, 2020)
Sexual assault cases have historically resulted in persistent victim dissatisfaction with, and alienation from, the prosecution process. As a result, some adversarial jurisdictions have moved contentiously towards integrating victim participation rights within the legal process to address sexual assault victims’ procedural and substantive justice concerns. The introduction of section 34 of the Sex Offenders Act 2001 (IRE), which allows a victim to access state-funded legal representation to oppose a defendant’s application for the introduction of the victim’s sexual history evidence in court, is one such example. Drawing from five interviews conducted with high-level criminal justice professionals, legal stakeholders and victim support workers, and an analysis of primary source documents, including legislation and reports, this article argues that, although section 34 represents a unique response to the problems raised by the use of a victim’s sexual history evidence in criminal trials, its shortcomings may hinder its capacity to improve sexual assault victims’ procedural justice experiences in ways unanticipated from its introduction.